Perspectives in medical virology. Volume 4, Human herpesvirus-6: epidemiology, molecular biology and clinical pathology - Ablashi, D. V. (Dharam V.); Krueger, G. R. F.; Salahuddin, S. Zaki.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1992)
This publication on HHV-6 is the first and so far only one where a composite picture of the virus is presented. Comprehensive accounts of HHV-6 biology, molecular virology, epidemiology and their association with diseases, including the effects of antiviral drugs, are covered in chapters contributed by leading researchers on HHV-6. The book is an excellent source of reference on HHV-6 for basic researchers, diagnostic virologists, clinicians, medical students and medical librarians since it provides the most current state-of-the-art information on HHV-6.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Human herpesvirus-6.; Human herpesvirus-6 infections; Human herpesvirus-6.; Human herpesvirus-6 infections; Electronic books